Meningkatkan Sinergi Pendidikan dan Pemberdayaan Pesantren Dalam Mewujudkan Generasi Santri Yang Mandiri dan Berdaya Saing - Julio, Muhammad; Fariiz, Abdurrahman; Al Ayyusuf, Muhammad Syufi; Hariyadi, Ade Puji; Aprilyani, Lutfia; Sari, Disya Asjaumi; Homsa, Anisa Nuraini; Rossa, Nia; Sari, Imas Hermala; Syarifah; Sari, Laela; Jefri Kurniawan; Dwi Wahyuningsih (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
The Real Work Lecture Program (KKN) aims to increase educational synergy and strengthen the empowerment of Islamic boarding schools. This activity was carried out for 30 days at the Al Wathoniyah Islamic Boarding School, with a focus on improving the quality of students through practice-based training and seminars. In its implementation, communication obstacles are overcome through regular meetings, a clear leadership structure, and an organized division of tasks to strengthen coordination. Despite facing communication challenges, the KKN program at Al Wathoniyah Islamic Boarding School has succeeded in improving the quality of education and skills of students. The steps implemented during this activity had a positive impact on the development of students and society.